USING INCIDENTAL VOCABULARY ACQUISITION TO ENRICH THE STUDENTS VOCABULARY MASTERY (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2015)
The research aimed to find out the improvement the students’vocabulary in terms of improving their understanding about of nouns and adjectives. To explain the increase, the researcher used a classroom action research (CAR) which was conducted in two cycles in which each cycle consisted of four meetings.The subject was the students at the eight grade of SMP Askari Pallangga Gowa. The number of samples consisted of 37 students. The research findings indicated that using Incidental Vocabulary Acquisition could improve the students’ vocabulary of noun and adjective.It was proved by the result of the diagnostic test, the students’ mean score got was 53.78. After applying the Incidental Vocabulary Acquisition in cycle I, the students’ achievement increased to be 63.6.  In cycle II the students’ vocabulary increased to be 85.